2011
DOI: 10.21236/ada546698
|View full text |Cite
|
Sign up to set email alerts
|

Acute Dermal Irritation Study of JP-8 and S-8 in New Zealand White Rabbits

Abstract: The objective of this study was to determine the irritative potential of JP-8, S-8 and a 50/50 volume/volume mixture of JP-8 and S-8 following a single exposure to the skin of albino rabbits. Three groups of three albino rabbits received a single, four-hour, occluded exposure and an additional three groups received a single, four-hour, semi-occluded exposure. Doses (0.5 mL) of the test substances were applied to clipped, unabraded skin. At the completion of all exposures, the bandages were removed and the site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…In a more recent study by Hurley et al (2011), JP-8 was also reported as slightly irritating under semioccluded exposure. However, the occluded exposure resulted in moderate irritation, the highest descriptive rating to date.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a more recent study by Hurley et al (2011), JP-8 was also reported as slightly irritating under semioccluded exposure. However, the occluded exposure resulted in moderate irritation, the highest descriptive rating to date.…”
Section: Discussionmentioning
confidence: 86%
“…Results from this rabbit skin irritation test varied: non-irritating ; slightly irritating (Kinkead et al, 1992); non-irritating (Wolfe et al, 1996); and moderately irritating (Hurley et al (2011). JP-8 is commonly combined with anti-icing and anti-corrosion chemicals, known as the JP-8+100 packages.…”
Section: Introductionmentioning
confidence: 99%
“…Petroleum-derived JP-8 (POSF 4658) has been tested previously, ranging from slightly to moderately irritating (Hurley et al, 2011;Mattie et al, 2013;Sterner et al, 2014). In the current study, JP-8 and HA JP-8 were both found to be slightly irritating; HA JP-8 appears to be somewhat less irritating, per the PDII score.…”
Section: Discussionmentioning
confidence: 99%
“…These fuels have had primarily aliphatic components. FT-SPK ranged from nonirritating to moderately irritating (Hurley et al, 2011;Sterner et al, 2014). The complete component analysis for FT-SPK, not previously published, can be found in Appendix H. FT-SPK is 99.84 percent aliphatic constituents by mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation